Psychiatric comorbidity among community-based, treatment seeking opioid dependents in Klang Valley - Azlin Baharudin,; Lotfi Anuar,; Suriati Saini,; Osman Che Bakar,; Rosdinom Razali,; Nik Ruzyanei Nik Jaafar, (Universiti Kebangsaan Malaysia, 2013)
The main objectives in this study were to determine the percentage of psychiatric comorbidity among treatment seeking opioid dependents in Klang Valley. A cross sectional study of opioid dependence patients was conducted between December 2007 and May 2008 at ten community-based drug substitution therapy clinics in Klang Valley. A total of 204 opioid dependence patients participated in the study using the structured clinical interview for DSM-IV Axis I disorders (SCID-I) as its instruments. The percentage of psychiatric comorbidity among opioid dependents was 43.6%. Major depressive disorder had the highest prevalence at 32.6%, followed by dysthymia at 23.6% and Panic disorder at 14.6%. Psychiatric comorbidity were found to have significant differences (p<0.05) in connection with history of polysubstance abuse, previous history of court sentences (legal status) and family history of psychiatric illnesses. This study showed that the percentage of psychiatric comorbidity is high among the opioid dependents. It highlights the urgent need for the psychiatric comorbidity to be assessed and early intervention is important for this group of patients.